Exploring hospitals' functional preparedness effective factors in response to disasters: a qualitative study in a lower middle-income country - Behrouz Samei; Javad Babaie; Jafar Sadegh Tabrizi; Homayoun Sadeghi-bazargani; Saber Azami Aghdash; Naser Derakhshani; Ramin Rezapour (BMC, 2024)
Abstract Background Medical services are among the most urgent needs of the disaster-affected population. Consequently, hospital preparedness -as the main health services provider- is one of the vital factors in effective response to disasters. The present study aims to explore the perspectives of study participants about the influential factors of hospital functional preparedness in a lower middle-income country. Methods In this qualitative study, data were collected through 17 semi-structured interviews with disaster management authorities selected by purposive sampling. Content-Analysis was used to analyze the data. Results 138 codes were developed and categorized into ten categories and 34 subcategories. The main categories were: 1- leadership, command, and coordination (4 subcategories); 2- risk assessment (3 subcategories); 3- legislating and developing protocols, guidelines, and programs (3 subcategories); 4- estimating and storing the necessary supplies and equipment (3 subcategories); 5- human resource management (4 subcategories); 6- education, training, and development of staff (6 subcategories); 7- vital routes and facilities (3 subcategories); 8- communication (3 subcategories); 9- security, safety and locating of safe zones (3 subcategories); 10- underlying disaster risk factors (2 subcategories). Conclusion According to the participants of this study, ten categories of factors can affect hospitals' functional preparedness; hospital managers and decision-makers can consider these factors to ensure the proper provision of medical services during disasters.